2015
DOI: 10.1038/srep17877
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature, Dry Transfer-Printing of a Patterned Graphene Monolayer

Abstract: Graphene has recently attracted much interest as a material for flexible, transparent electrodes or active layers in electronic and photonic devices. However, realization of such graphene-based devices is limited due to difficulties in obtaining patterned graphene monolayers on top of materials that are degraded when exposed to a high-temperature or wet process. We demonstrate a low-temperature, dry process capable of transfer-printing a patterned graphene monolayer grown on Cu foil onto a target substrate usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…Moreover, polydimethylsiloxane (PDMS), which is the most widely used material for the elastomer stamps used in transfer printing, swells due to the presence of organic solvents such as acetone, dissolving the polymer carrier material. Swelled PDMS can cause cracks on graphene film, which degrade the electrical and mechanical performances of graphene . As a result, an alternative carrier material has been researched for the production of high‐quality transferred graphene by transfer printing .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, polydimethylsiloxane (PDMS), which is the most widely used material for the elastomer stamps used in transfer printing, swells due to the presence of organic solvents such as acetone, dissolving the polymer carrier material. Swelled PDMS can cause cracks on graphene film, which degrade the electrical and mechanical performances of graphene . As a result, an alternative carrier material has been researched for the production of high‐quality transferred graphene by transfer printing .…”
Section: Introductionmentioning
confidence: 99%
“…The extraction of water between graphene and the elastomer stamp can break the graphene structure due to the high surface tension of water. Cha et al reported a low‐temperature dry transfer‐printing process using a patterned graphene monolayer with Au thin film as a carrier material and a water‐ethanol mixture to lower the surface tension . No damage to the graphene from dissolving of the PDMS stamp was observed when using the Au thin film as the carrier material.…”
Section: Introductionmentioning
confidence: 99%
“…However, these approaches require exquisite manipulations and are not universally achievable since the material‐substrate adhesion differs much with various growth conditions. Soaking CVD‐grown 2DLMs in water can also bring cracks to the materials resulting from the hydrophobic nature of 2DLMs . Another common problem of these methods is that the exfoliation is not on‐target, i.e., the entire 2D material on the substrate is transferred at one time, causing inevitable waste of materials.…”
mentioning
confidence: 99%
“…7,30,31 To transfer the PEDOT layer directly onto a soft PDMS layer, a dry transfer method could be explored and used to take advantage of the curing-induced detachment properties of the PDMS surface. 32,33 This dry transfer method would be essential to maintain the doping state of the PEDOT layer because the method does not use a solvent or any additives.…”
Section: Introductionmentioning
confidence: 99%